An analysis of the effectiveness of Affirmative Action in promoting gender balance in Zimbabwe - Ndlovu, Thenjiwe (2017)
This study explored an analysis of the effectiveness of Affirmative Action in promoting gender balance in Zimbabwe. The study is hinged on the feminism theory which served as its theoretical framework. In investigating issues surrounding the adoption and implementation of the Affirmative Action programmes and policies in Zimbabwe, the researcher made use of the explanatory research techniques to generate data. Qualitative research techniques were employed by the researcher. In-depth interviews with key informants who were selected using purposive sampling and documentary research and informal conversational interviews were used to generate qualitative data. Qualitative data analysis was hinged on thematic and content analysis. Research findings established that Affirmative Action in promoting gender balance is still far from achieving the targeted results of equal representation between women and men in all spheres of life in Zimbabwe. The study concluded by recommending that there is need for change in attitude of people both women and men and more compulsory awareness campaigns must be conducted countrywide in order to sensitise both women and men on the need and importance of having equal representation. It was noted that for Affirmative Action to be more active a bottom up approach must be used also more action should be directed to the social livelihood of people because thus where lies the backbone of the people’s lives. Constant monitoring and evaluation of the Affirmative Action policies and programmes has to be conducted in order to achieve positive results.